MAGNETITE ACTIVITIES ACROSS THE MGAL2O4-FE3O4 SPINEL JOIN, WITH APPLICATION TO THERMOBAROMETRIC ESTIMATES OF UPPER MANTLE OXYGEN FUGACITY - Mattioli, G; Wood, B (Springer-Verlag, 1988)
The activity of Fe3O4 component in MgAl2O4-Fe3O4 spinels has been measured at 900° and 1000° C and 1 atm total pressure using a zirconia oxygen electrolyte. As previously reported for the dilute Fe3O4 concentration region (Mattioli and Wood 1986a), magnetite activity at 1000° C is greater than at 900° C at constant Fe3O4 mole fraction, for compositions across the MgAl2O4-Fe3O4 join between 20 and 80 mol% Fe3O4 component. The 1-atm solvus crest lies between 900° and 1000° C and, at 900° C the limbs are at Fe3O4 mole fractions of 0.2 and 0.6 approximately. Application of the O'Neill and Navrotsky (1983, 1984) cation distribution model indicates that the unusual activity - composition behavior of Fe3O4 is caused by changes in the equilibrium state of disorder of mixed MgAl2O4-Fe3O4 spinels relative to the disordered Fe3O4 standard state. In addition, both stoichiometric volumes (Mattioli et al. 1987) and activities across the MgAl2O4-Fe3O4 join suggest that short range order is significant for this binary. Excess free energy terms must be added to "ideal" Fe3O4 activities formulated from equilibrium cation distributions in complex MgAl2O4-Fe3O4 spinels in order to increase Fe3O4 activities to values consistent with observation and to generate the apparent region of immiscibility at 900° C. We have applied our activity data to the estimation of upper mantle spinel-lherzolite oxygen fugacities. We calculated that minimum Mathematical expression's are about 2 log units below the synthetic QFM buffer at 15 kbar total pressure for Fe3O4 concentration of 2 mol%, in a Cr-free spinel phase. If a preliminary calibration of an additional 25 mol% Fe2+-substitution as FeCr2O4 or FeAl2O4 component is incorporated into Fe3O4 activity, then olivine-orthopyroxene-spinel assemblages of depleted-Type 1-spinel-lherzolite xenoliths indicate Mathematical expression's close to QFM at 15 kbar. This is in good agreement with previous thermobarometric Mathematical expression estimates and in sharp contrast to 1 atm intrinsic Mathematical expression measurements near IW. © 1988 Springer-Verlag.